Efficient Synthesis of O-tert-Propargylic Oximes via Nicholas Reaction - Nakamura, Itaru; Shiga, Keigo; Suzuki, Mao; Terada, Masahiro (Synthesis, 2020)
A synthetic protocol to access O-tert-propargylic oximes derived from tertiary propargylic alcohols was established via Nicholas reaction. Thus, BF3·OEt2-mediated reaction between the dicobalt hexacarbonyl complex of tert-propargylic alcohols and p-nitrobenzaldoxime followed by decomplexation with cerium(IV) ammonium nitrate afforded the corresponding O-tert-propargylic oximes in good to high yields. The obtained O-tert-propargylic oximes were effectively converted into heterocycles, such as four-membered cyclic nitrones, oxazepines, and isoxazolines, by using π-Lewis acidic catalysts.
Keywords: Nicholas reaction; alkynes; tertiary alcohols; heterocycles; gold catalysts; spirocycles